2015
DOI: 10.5812/iranjradiol.18286
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Measurement in Carotid Artery: Quantitative Comparison of Time-Resolved 3D Phase-Contrast MRI and Image-based Computational Fluid Dynamics

Abstract: Background:Understanding hemodynamic environment in vessels is important for realizing the mechanisms leading to vascular pathologies.Objectives:Three-dimensional velocity vector field in carotid bifurcation is visualized using TR 3D phase-contrast magnetic resonance imaging (TR 3D PC MRI) and computational fluid dynamics (CFD). This study aimed to present a qualitative and quantitative comparison of the velocity vector field obtained by each technique.Subjects and Methods:MR imaging was performed on a 30-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The comparison between velocity color maps along the descending aorta further confirmed the accuracy of the FSI model, which also captured late systolic secondary flow features that were not detected by 4D flow owing to its lower spatial resolution. Also, RMSE between velocity magnitude color maps ranged from 16% to 36%; despite the higher complexity of our fluid domain, these results are in agreement with a previous study focused on the CFD vs. 4D flow comparison in a carotid artery (Sarrami-Foroushani et al, 2015), which reported RRMSE values ranging from 10% to 20%.…”
Section: Discussionsupporting
confidence: 91%
“…The comparison between velocity color maps along the descending aorta further confirmed the accuracy of the FSI model, which also captured late systolic secondary flow features that were not detected by 4D flow owing to its lower spatial resolution. Also, RMSE between velocity magnitude color maps ranged from 16% to 36%; despite the higher complexity of our fluid domain, these results are in agreement with a previous study focused on the CFD vs. 4D flow comparison in a carotid artery (Sarrami-Foroushani et al, 2015), which reported RRMSE values ranging from 10% to 20%.…”
Section: Discussionsupporting
confidence: 91%
“…In the patient-specific model for transient simulation, we imposed physiological pressure waveform (range: 72–129 mmHg, Figure 1C ) at the ICA inlet ( Sarrami-Foroushani et al, 2015 ). Due to the lack of in vivo measurements of flow velocity at MCA/ACA outlets, we adopted 3-element Windkessel models, to avoid possible errors caused by possibly inaccurate assumptions in blood pressure or flow rate ( Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
“…It is a feasible method of measuring the 3D distribution of the blood velocity vector field in vivo, allowing 3D flow structures to be examined with a single scan [10,11]. 4D flow MRI has been used to obtain data about the blood-flow characteristics of the cerebral vascular system, the aorta, as well as the carotid arteries, and can highlight local and global hemodynamic conditions [5,8,9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%